1999
DOI: 10.1159/000045490
|View full text |Cite
|
Sign up to set email alerts
|

Immunogold Labelling of Cytokines in Glomeruli in Children with Various Renal Diseases

Abstract: Precise localization of cytokines such as transforming growth factor-β (TGF-β), tumor necrosis factor-α (TNF-α), interleukin (IL)-1 and IL-6 was observed in glomeruli using immunogold electron microscopy in 21 children with various types of renal diseases. The distribution pattern of these cytokines, as well as immunoglobulins, C3c and fibrinogen (Fg), was essentially confined to the electron-dense deposits (EDDs) regardless of their location. Frequency of positive labelling of each cytokine was different amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
2
12
1
Order By: Relevance
“…During lupus, aberrant laminin ␤1 is produced by the endothelium and by podocytes ( Figure 5H). We also found that the TGF␤1 content was confined to the EDDs (Figures 5A-D), as previously described by other investigators using lower-resolution light microscopy (23,24). The specific ligand for TGF␤1 trapping within the EDDs, however, was not investigated in the present study.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…During lupus, aberrant laminin ␤1 is produced by the endothelium and by podocytes ( Figure 5H). We also found that the TGF␤1 content was confined to the EDDs (Figures 5A-D), as previously described by other investigators using lower-resolution light microscopy (23,24). The specific ligand for TGF␤1 trapping within the EDDs, however, was not investigated in the present study.…”
Section: Resultssupporting
confidence: 90%
“…Interestingly, TGF␤1 has also been found by us and by other investigators to be confined to the EDDs in lupus nephritis (23,24). Consumption in the kidney may reflect lower circulating levels of TGF␤1, which seem to be associated with severe disease, kidney involvement, and worse outcome in SLE (35,36).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Mesangial and proximal tubular cells are known to secrete TNFa [25], and this cytokine has been detected in the glomeruli of patients with MLNS in relapse by in situ hybridization [26]. Cho et al recently reported increased urinary TNFa excretion in IMLNS patients in relapse when compared with normal controls or MLNS patients in remission [22].…”
Section: Discussionmentioning
confidence: 99%